Good and Correct Use of Indonesian in Conversing on Social Media - A Ibrahim, Riza; Azkiyah S, Hilda (International Journal of Linguistics, Communication, and Broadcasting, 2024)
Indonesian is an important language in the territory of the Unitary State of the Republic of Indonesia. Judging from its position in the treasures of national and state life, Indonesian has two meanings, namely as a national language and as a state language. Speaking well and correctly is the key to successful communication. The right language ensures that the message you want to convey can be clearly understood by the recipient. Mistakes in word choice or grammar can cause confusion or even misunderstandings. This paper aims to conduct a study of the good and correct use of Indonesian in social media. This study was carried out using the library research method by utilizing articles, journals and internet access as sources. In this study, various effects that can be caused are considered. Logically, based on social media language, this issue is considered important to receive special attention. Based on the data and information collected, it shows that many social media users use a mixture of Indonesian and their mother tongue and even foreign languages to express their thoughts and feelings.